Advanced modelling techniques studying global changes in environmental sciences - Park, Young-Seuk; Lek, Sovan; Baehr, Christophe; Jnsen, Sven Erik, 1934- (Amsterdam, Netherlands: Elsevier, 2015)
Advanced Modelling Techniques Studying Global Changes in Environmental Sciences discusses the need for immediate and effective action, guided by a scientific understanding of ecosystem function, to alleviate current pressures on the environment. Research, especially in Ecological Modeling, is crucial to support the sustainable development paradigm, in which the economy, society, and the environment are integrated and positively reinforce each other. Content from this book is drawn from the 2013 conference of the International Society for Ecological Modeling (ISEM), an important and active research community contributing to this arena. Some progress towards gaining a better understanding of the processes of global change has been achieved, but much more is needed. This conference provides a forum to present current research using models to investigate actions towards mitigating and adapting to change.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 14, 2015).
Elsevier
Keywords: Ecology -- Simulation methods; Ecosystem management -- Simulation methods; Environmental sciences -- Simulation methods; Global environmental change; NATURE / Ecology; NATURE / Ecosystems & Habitats / Wilderness; SCIENCE / Environmental Science; SCIENCE / Life Sciences / Ecology; Ecology -- Simulation methods; Ecosystem management -- Simulation methods; Environmental sciences -- Simulation methods; Global environmental change; Electronic books